x2 +(3–2a)x – 6a=0
Asked by sarthakuniyal149 | 30th Mar, 2019, 02:09: PM
x2 - (3 - 2a)x - 6a = 0
Comparing with ax2 + bx + c = 0
a = 1, b = -(3 - 2a), c = -6a
b2 - 4ac = (3 - 2a)2 - 4 (1) (-6a)
= 9 - 12a + 4a2 + 24a
= 4a2 + 12a + 9
= (2a + 3)2
Using formula we get x as 3 or -2a.
Answered by Sneha shidid | 30th Mar, 2019, 02:31: PM
- 2/3 and 1 are solutions of equation mx^2+nx+6=0. find the values of m and n.
- please solve it .
- 1/(2a+b+2x)=1/2a+1/b+1/2x I hope u understand the question...in words it is - one upon twice of a plus b plus twice of x equals one upon twice of a plus one upon b plus one upon twice of x
- (x^2-x)^2+5(x^2-x) +4=0
- 25x^2+30x+7=0 solve by formula
- X^2-3 (x+3)=0
Kindly Sign up for a personalised experience
- Ask Study Doubts
- Sample Papers
- Past Year Papers
- Textbook Solutions
Verify mobile number
Enter the OTP sent to your number